UPAYA MEWUJUDKAN KELUARGA SAKINAH DALAM KELUARGA KARIR - Fathurrahman, Imam; Tirmidzi, Tirmidzi (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
Realizing the family of sakinah mawaddah and rohmah is the hope of every married couple. How happy to have a family filled with mutual love, love, protect and respect. But apparently realizing a family like that is not the work of turning the palm of the hand. It takes great effort and support from all parties in the family both father, mother and child. The role of the father is very important who acts as a priest who will lead his family in earning a living, providing security in the family. However, it is not uncommon for them to find a dead end, both with material kissing and the needy.